Telaah Keterlibatan Masyarakat Sipil dalam Tata Kelola ASEAN - Wahyu Rozzaqi Ginanjar; Ali Maksum (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
ASEAN is facing criticism in its journey towards a regional organization that involves civil society participation based on Vision 2020 which was first introduced on 15 December 1997. Whereas after the regional financial crisis in 1997-1998, ASEAN leaders began to promote people-oriented ideas in Southeast Asia. Thus, this paper aims to explain the mechanism for involving civil society in ASEAN governance. The logic of appropriateness about the involvement of civil society in the policy-making process at global institutions becomes a theoretical framework for understanding implementation in regional organizations. This study applies a qualitative analysis method. The technique of collecting data is through literature study that relies on research publications, government reports, and internet-based literature. The results of the study understand that the ASEAN Charter and Guidelines for Affiliation of Civil Society Organizations 2012 are official documents that contain rules for ASEAN in opening up space for civil society involvement in governance in ASEAN. There are three mechanisms for involving civil society in ASEAN governance, namely affiliates, ad hoc consultations and GO-NGO forums. The contribution of civil society is adjusted to the prevailing institutional objectives. However, these three participation mechanisms serve to limit civil society organizations from using these channels to challenge policies or propose alternative agendas.